Environmental Impact Assessment with LCA - Denac, Matjaž (Mastering Sustainability in Supply Chains, 2026)
Every activity can be correlated with environmental impacts. However, designing effective measures to reduce them requires an evaluation of the impacts first. To date, life cycle assessment (LCA) is the only standardised and most comprehensive method for assessing environmental impacts. Slovenian companies do not use the LCA method to the same extent as their competitors abroad and therefore cannot take advantage of the benefits that LCA can offer. LCA is a job for engineers and can only be carried out by trained professionals with a broad knowledge of materials, technologies, energy, appropriate software and access to databases. However, an LCA cannot be carried out without the client's input and notification of the intended use of the results. The purpose of this material is therefore to understand what an LCA is, how an LCA project should be designed so that contractors can prepare a suitable tender for the LCA service and then carry out the assessment. In order to avoid misleading expectations on the part of potential clients, some examples of the results of LCA studies will be presented. The reader will thus learn what data the client has to provide, in what form and how it will be used. The knowledge provided will be useful for all those who are confronted with the need to evaluate environmental impacts and demonstrate environmentally responsible business performance.